Comprehensive characterization of γ-aminobutyric acid (GABA) production by Levilactobacillus brevis CRL 2013: insights from physiology, genomics, and proteomics - Cataldo, Pablo G.; Urquiza Martínez, María Paulina; Villena, Julio; Kitazawa, Haruki; Saavedra, Lucila; Hebert, Elvira M. (Frontiers in Microbiology, 2024)
Introduction Levilactobacillus brevis CRL 2013, a plant-derived lactic acid bacterium (LAB) with immunomodulatory properties, has emerged as an efficient producer of γ-aminobutyric acid (GABA). Notably, not all LAB possess the ability to produce GABA, highlighting the importance of specific genetic and environmental conditions for GABA synthesis. This study aimed to elucidate the intriguing GABA-producing machinery of L. brevis CRL 2013 and support its potential for safe application through comprehensive genome analysis. Methods A comprehensive genome analysis of L. brevis CRL 2013 was performed to identify the presence of antibiotic resistance genes, virulence markers, and genes associated with the glutamate decarboxylase system, which is essential for GABA biosynthesis. Then, an optimized chemically defined culture medium (CDM) was supplemented with monosodium glutamate (MSG) and yeast extract (YE) to analyze their influence on GABA production. Proteomic and transcriptional analyses were conducted to assess changes in protein and gene expression related to GABA production. Results The absence of antibiotic resistance genes and virulence markers in the genome of L. brevis CRL 2013 supports its safety for potential probiotic applications. Genes encoding the glutamate decarboxylase system, including two gad genes (gadA and gadB) and the glutamate antiporter gene (gadC), were identified. The gadB gene is located adjacent to gadC, while gadA resides separately on the chromosome. The transcriptional regulator gadR was found upstream of gadC, with transcriptional analyses demonstrating cotranscription of gadR with gadC. Although MSG supplementation alone did not activate GABA synthesis, the addition of YE significantly enhanced GABA production in the optimized CDM containing glutamate. Proteomic analysis revealed minimal differences between MSG-supplemented and non-supplemented CDM cultures, whereas YE supplementation resulted in significant proteomic changes, including upregulation of GadB. Transcriptional analysis confirmed increased expression of gadB and gadR upon YE supplementation, supporting its role in activating GABA production. Conclusion These findings provide valuable insights into the influence of nutrient composition on GABA production. Furthermore, they unveil the potential of L. brevis CRL 2013 as a safe, nonpathogenic strain with valuable biotechnological traits which can be further leveraged for its probiotic potential in the food industry.